Fossil-wood carbon-isotope stratigraphy of the non-marine Wealden group (Lower cretaceous, southern england) - Robinson, SA; Hesselbo, S (2004)
Fossil-wood carbon-isotope data are presented for the Wessex Formation, a non-marine unit within the Lower Cretaceous (Valanginian-Barremian) Wealden Group of the Isle of Wight and Dorset, southern England. The carbon-isotope values have a range (δ13C c. -26.6 to -19.8‰) that is consistent with that expected for Mesozoic C3 plants. Consideration of the Isle of Wight fossil-wood carbon-isotope data together with data from Dorset allows construction of a composite fossil-wood carbon-isotope curve for almost the entire Wealden Group. The new carbon-isotope curve is in smooth continuity with data previously published from the overlying lagoonal Vectis Formation and marine Lower Greensand Group of Aptian age. A tentative correlation with a Tethyan reference carbon-isotope curve allows the provisional application of stage-level chronostratigraphy to the Wealden Group. Correlations suggest that the Wealden Group sediments are dominantly of Hauterivian and Barremian age and that the Valanginian is either condensed or partially missing. The carbon-isotope data presented indicate that even during times of relative carbon-cycle quiescence atmosphere CO2 faithfully tracks the carbon-isotopic composition of the oceanic reservoir.